Penguatan Perilaku Hidup Bersih dan Sehat (PHBS) melalui Edukasi dan Pemberdayaan Masyarakat di Puskesmas Pembeliangan Kecamatan Sebuku Kabupaten Nunukan - Muhammad Muhammad; Byba Melda (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aimed to improve community knowledge and awareness of Clean and Healthy Living Behavior (PHBS) in the working area of Pembeliangan Public Health Center, Sebuku District, Nunukan Regency. The program was implemented through health education using lectures, interactive discussions, question-and-answer sessions, demonstrations of PHBS practices, and the distribution of educational leaflets and posters. The materials covered handwashing with soap, the use of clean water, environmental sanitation, and household waste management. The results showed increased community knowledge and awareness of PHBS. Participants were actively involved in the educational activities and practical demonstrations, while the participation of community health volunteers and local leaders supported the sustainability of PHBS implementation.